A Study on the Value Destruction Caused by Incomplete Interaction Behaviors on a Live Shopping Platform - Tser-Yieth, Chen; Pei-Fang, Li; Tzu-Han, Hsu (Journal of Management World, 2024)
This study aims to understand the impact of incomplete interaction behaviors on value destruction in online shopping. Incomplete interaction behaviors include incomplete product interaction, incomplete information interaction and incomplete parasocial interaction. Additionally, negative interpersonal and intrapersonal relationships are used as mediators in this study. Views were collected from 522 users in Taiwan who have used livestream platforms for shopping and had negative experiences. An online questionnaire was designed and sent to livestreaming customers, and quota sampling was employed to enhance the sample representativeness. The empirical results were produced by covariance-based structural equation modeling with AMOS and show that incomplete parasocial interaction has the greatest impact on value destruction via negative interpersonal relationships. The negative intrapersonal relationships were not found to have mediation effects in this study. The practical implications for individuals who plan to join the livestream shopping industry are not only able to showcase products, but also appropriately disclose their personas to build relationships with customers and interact with those who show their emotions or views. Managing customer-to-customer interactions in the livestreaming process is equally important, as negative feelings among customers directly result in value destruction. In other words, streamers should focus on training themselves in the aspects of what product and personal information should be disclosed to the public and focus on observing and managing the feelings and emotions of their live customers as well as the consumer-to-consumer relationships.